Dynamic Control of Mobile Robot Using RBF Global Fast Sliding mode - Ali Mallem; Noureddine Slimane; Walid Benaziza (IAES International Journal of Robotics and Automation (IJRA), 2018)
This paper mainly In this paper a dynamic control of mobile robot using RBF global fast sliding mode (RBF-GFSM) strategy is presented. Firstly a GFSM controller is used in order to make the linear and angular velocities converge to references ones in finite time. However a problem of instability of velocities is appeared by introducing disturbances in the system. Secondly, a combined controller using RBF-GFSM approach is applied in aim to stabilize the velocities errors and estimates the nonlinear function of the robot model. The system stability is done using the lyapunov theory. The proposed controllers are dynamically simulated using Matlab/Simulink and the simulations results show the efficiency and robustness of the proposed control strategy.